Pengaruh Keterikatan Kerja, Karakteristik Pekerjaan, dan Karakteristik Individu Terhadap Budaya Organisasi di PT. Perkebunan Nusantara III - Rozi, Fakhrur; Syaifuddin, Syaifuddin; Lubis, Yusniar (Universitas Medan Area, 2021)
This study aims to determine and analyze the effect of Work Engagement, Job Characteristics and Individual Characteristics on Organizational Culture. This research is verificative and descriptive, using descriptive survey methods and explanatory survey methods. The sample was determined by random sampling method as many as 242 executive employees at the office of the director of PTPN III. Data collection through questionnaires. Data were analyzed using multiple linear regression analysis. The results showed that partially, work engagement, job characteristics, and individual characteristics had a positive and significant effect on the performance of the implementing employees at the Office of the Director of PTPN III. The highest effect value is the Individual Characteristics variable, meaning that individual characteristics have a more dominant influence on employee performance, with a total influence of 28.5%. Simultaneously, Work Engagement, Job Characteristics and Individual Characteristics have a positive and significant effect on the Implementing Organizational Culture at the Office of the Director of PTPN III.